Effectiveness of Automation Studio Software in Enhancing Electrical Engineering Students’ Skills in Designing PLC Ladder Diagrams - Endryansyah, Endryansyah; Suprianto, Bambang; Rusimamto, Puput (Journal of Technical Education and Training, 2026)
The growing complexity of industrial automation requires Electrical Engineering students to develop higher skills in the area of Programmable Logic Controller (PLC) programming, more specifically on ladder diagram design. The conventional methods often lack sufficient interaction, practice, and actual industry exposure for the students. In this regard, this study aims to determine whether or not Automation Studio Software is effective in developing students’ abilities in designing PLC ladder diagrams. A quasi-experimental study was conducted with 30 students for each experimental and control class. The experimental class was taught using Automation Studio, whereas the control class used conventional method of teaching. The instruments included a validated performance test and a student perception survey questionnaire. Results show a significantly improved post-test score for the experimental class by 40.96%, with an N-Gain of 74.96% which falls under moderate category and a very large effect size. Students’ perceptions were overwhelmingly positive, 87% reporting enhanced understanding and 92% recommending the integration of the software in the curriculum. This implies that Automation Studio Software presents an industry-based learning environment that is capable of bridging the gap between theory and practice, improving student PLC programming competencies.